A minimalist cardio-oncology service: A personal experience from Wales - Riaz Muhammad Hamza; Barrington Craig; Ionescu Adrian (Romanian Journal of Cardiology)
Cardio-oncology is intensely ‘hyped’ in cardiology circles, and there are good reasons for advocating a formal integration of the 2 specialties, but so far evidence of a benefit from the collaboration has not emerged. We provide a simplified blueprint for a ‘minimalistic’ service, based on our own practice and experience in Wales, UK.